sinusoidal inequalities

May 2010
8
0
How can I from the following inequality

(cosq1cosq1) + (cosq2cosq2) +(cosq3cosq3) - 2 cosq1 cosq2 cosq3-1 ≤ 0

Drive the following inequality
cosq1 cosq2 – sqrt[(sinq1sinq1)(sinq2sinq2)]≤ cosq3 ≤ cosq1 cosq2 +sqrt[(sinq1sinq1)(sinq2sinq2)]


sqrt == square root

Please help
 
Nov 2009
468
14
Are you sure this isn't supposed to be in the University section? If nobody has answered it yet, you might have to post it there
 
May 2010
8
0
Thanks i will post it in university section